Molecular and functional characterization of a spermidine transporter (TcPAT12) from Trypanosoma cruzi - Carrillo, Carolina (2006)
Trypanosoma cruzi, the etiological agent of Chagas' disease, is the only eukaryotic cell which lacks the ability to synthesize polyamines de novo. In this work, we describe for the first time the molecular and biochemical properties of a high-affinity spermidine transporter from T. cruzi. The transporter gene TcPAT12 was functionally expressed in Xenopus laevis oocytes, showing high levels of spermidine uptake. Similar apparent affinity constants for spermidine uptake were obtained when comparing T. cruzi epimastigotes and heterologous expressed TcPAT12 in X. laevis. In addition, TcPAT12 also transports putrescine and the amino acid l-arginine at lower rates than spermidine.